SEMANTICS OF ADJECTIVE NOUNS (ON THE BASIS OF THE GERMAN LANGUAGE MATERIAL) - G. P. Kuzikevich (Наука и техника, 2006)
The paper considers reasons of semantic heterogeneity of abstract adjective-type nouns. A number of conceptual signs of abstract nouns being revealed on the basis of the German language material is given in the paper.